(untitled) (Scientific journal of the Fergana State University, 2024)
The importance of artistic translation in literature, the great role of translation in the emergence of common social-political, literary-aesthetic laws in national cultures and national literature, and translation has educational and educational value. The meaning of the concept of translation is very broad. From one language to another, fiction, poetry, dramatic and prose works, scientific and scientific-popular books on various fields of science, diplomatic documents, official papers, articles of political figures and speeches of orators, newspaper materials; conversations of people speaking other languages ​​who need the services of an "interpreter" are translated, movies are translated from one language to another. Literary translation is a field of artistic creativity. Because, unlike other branches of translation, literary translation has its own characteristics. These features come from the nature of fiction. For example, if the main thing in science is evidence, analysis, and scheme, in a work of art the image, image, and the impressiveness of the story being told are important.